2006
DOI: 10.1089/ten.2006.12.ft-95
|View full text |Cite
|
Sign up to set email alerts
|

Lentiviral Manipulation of Gene Expression in Human Adult and Embryonic Stem Cells

Abstract: Human stem cells could revolutionize the field of medicine by providing a diverse range of cell types for tissue replacement therapies and drug discovery. To achieve this goal, genetic tools need to be optimized and developed for controlling and manipulating stem cells ex vivo. Here we describe a lentiviral delivery system capable of high infection rates in human mesenchymal and embryonic stem cells. The lentiviral backbone was modified to express mono-and bi-cistronic transgenes and was also used to deliver s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…McMahon et al [78] have shown the superiority of lentiviral gene delivery to rat MSCs over other viral or nonviral gene delivery methods. Other studies reported the ability of lentiviral vectors to transduce human [79][80][81][82][83] or mouse [84] MSCs and sustain transgene expression longer than other viral and nonviral vectors. These studies have also indicated that the transduction procedure itself does not affect the growth, differentiation potential, and migration capacity of MSCs and does not induce excessive cell death.…”
Section: Genetic Manipulation Of Mscsmentioning
confidence: 99%
“…McMahon et al [78] have shown the superiority of lentiviral gene delivery to rat MSCs over other viral or nonviral gene delivery methods. Other studies reported the ability of lentiviral vectors to transduce human [79][80][81][82][83] or mouse [84] MSCs and sustain transgene expression longer than other viral and nonviral vectors. These studies have also indicated that the transduction procedure itself does not affect the growth, differentiation potential, and migration capacity of MSCs and does not induce excessive cell death.…”
Section: Genetic Manipulation Of Mscsmentioning
confidence: 99%
“…The lentiviral vector G-P, which expresses short hairpin RNA (shRNA)-GFP, was described previously (9), and lentiviral vector X-P was generated using oligonucleotide 5Ј-CGA AAA AGA CTG CCA GAG ATC GAA AGA AGG CGA ACC TTC TCT CAA TCT CCG GCA GTC GGT GTT TCG TCC TTT CCA CAA GAT-3Ј and T7 oligonucleotide 5Ј-TAA TAC GAC TCA CTA TAG GG-3Ј to PCR amplify an shRNA expression cassette, using pGEM-U6L as a template (9). This amplicon was cloned using pGEM-T-Easy (Promega) and inserted into pCSPW as described previously (9).…”
Section: Rna Extraction and Reverse Transcriptase-pcr (Rt-pcr)mentioning
confidence: 99%
“…This amplicon was cloned using pGEM-T-Easy (Promega) and inserted into pCSPW as described previously (9). The shRNA sequences are therefore shRNA-GFP (5Ј-GUU CAU CUG CAC CAC CGG CAA GCU UCG GCU UGC CGG UGG UGC AGA UGA ACU U-3Ј) and shRNA-XBP)5Ј-GAC UGC CGG AGA UUG AGA GAA GGU UGC CCU UCU UUC GAU CUC UGG CAG UCU U-3Ј).…”
Section: Rna Extraction and Reverse Transcriptase-pcr (Rt-pcr)mentioning
confidence: 99%
“…Generally, viral (e.g., adenoviruses, lentiviruses and retroviruses) and nonviral vectors (e.g., lipids and polymers) can be used for cellular transfection and/or nucleofection, thus offering durable gene expression within stem cells [93][94][95][96]. Nonviral carriers have a number of advantages over viral vectors, since they exhibit low-risk immunogenicity and insertional mutagenesis, controllable toxicity, and excellent gene-carrying capacity [95].…”
Section: A U T H O R P R O O Fmentioning
confidence: 99%